Isolation, culture expansion and characterization of canine bone marrow derived mesenchymal stem cells - D Kazemi; K Shams Asenjan; N Dehdilani; H Parsa; A.A Movassagh Pour Akbari; P Akbarzadeh (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2016)
The purpose of the present study was to isolate, culture expand and characterize canine bone marrow derived mesenchymal stem cells. Bone marrow aspirates of 15 adult male dogs were collected to this end and their mononuclear cells isolated by centrifugation and cultured in standard media. The adherent cells were isolated and their mesenchymal origin was confirmed at 3rd passage by cellular morphology, expression of surface antigens and differentiation to osteogenic and adipogenic lineage. After 4 days, spindle shaped fibroblast like cells which were apparently bone marrow derived mesenchymal stem cells appeared in culture medium and their numbers increased over time. The cells reached 3rd passage with over 75% confluent after a mean of 22.89±5.75 days. Flow cytometric analysis revealed that the cells negatively expressed CD34 and CD45 antigens while positively expressing CD44 and CD105 antigens. Differentiation into osteogenic and adipogenic lineage had taken place after one month culture in induction medium. VDR, COL1A1, BGLAP and SPARC gene expression indicated that mesenchymal stem cells isolated from canine bone marrow had differentiated into osteogenic lineage. These findings can form the basis of any forthcoming clinical studies involving the use of canine mesenchymal stem cells particularly in the field of bone and cartilage regeneration.